Effects of mosapride on secondary peristalsis in patients with ineffective esophageal motility. (December 2013) - Chen, Chien-Lin; Yi, Chih-Hsun; Liu, Tso-Tsai; Orr, William C.
Abstract Objective. Ineffective esophageal motility is frequently found in patients with gastroesophageal reflux diseases. Secondary peristalsis contributes to esophageal acid clearance. Mosapride improves gastrointestinal (GI) motility by acting on 5-hydroxytrypatamine4 receptors. The authors aimed to evaluate the effect of mosapride on secondary peristalsis in patients with ineffective esophageal motility. Material and methods. After recording primary peristalsis baseline, secondary peristalsis was stimulated by slowly and rapidly injecting mid-esophageal air in 18 patients. Two separate experiments were randomly performed with 40 mg oral mosapride or placebo. Results. Mosapride had no effect on the threshold volume of secondary peristalsis during slow air distension (9.8 ± 0.97 vs. 10.2 ± 1.0 mL; p = 0.84), but decreased the threshold volume during rapid air distension (4.1 ± 0.2 vs. 4.6 ± 0.3 mL; p = 0.001). The efficiency of secondary peristalsis during rapid air distension increased with mosapride (70% [40–95%]) compared with placebo (60% [10–85%]; p = 0.0003). Mosapride had no effect on the amplitudes of distal pressure wave of secondary peristalsis during slow (94.3 ± 9 vs. 101.9 ± 9.1 mmHg; p = 0.63) or rapid air distension (89.3 ± 9 vs. 95.2 ± 8.3 mmHg; p = 0.24). Conclusions. Mosapride improves esophageal sensitivity of secondary peristalsis by abrupt air distension but has limited effect on the motor properties of secondary peristalsis in ineffective esophageal motility patients. Despite its well-known prokinetic effect, mosapride enhances the efficiency of secondary peristalsis in patients with ineffective esophageal motility through augmenting esophageal sensitivity instead of motility.